Microwave Breast Imaging by the Filtered ForwardBackward Time-Stepping Method - Kismet, Hong Ping; Takenaka, Takashi; Moriyama, Toshifumi; Yamasaki, Takafumi (2010)
In this paper, an inverse scattering technique referred to as the filtered forward-backward time-stepping method is applied to microwave imaging for breast cancer detection. A two-dimensional numerical breast phantom (derived from MR images) with high contrast between fat and fibroglandular tissues, and low contrast between fibroglandular and tumor tissues are used to assess the efficacy of the proposed method.